HUBUNGAN SANITASI KAPAL DENGAN KEBERADAAN VEKTOR PENYAKIT DAN RODENT PADA KAPAL PENUMPANG DI PELABUHAN MERAK PROVINSI BANTEN - Burhanuddin Thohir; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Merak Port Banten Province is the most populous crossing port in Indonesia. Data of sanitation supervision of passenger ship transportation equipment at Merak harbor conducted by officer of Port Health Office (KKP) Class II Banten, during the period of 2015-2016 the number of vessels that have been inspected free of vector and rodent and carried out sanitary ship free from vector and rodent tends to increase from 28 ships to 75 ships. In the examination of some places that are found are kitchen, passenger room, warehouse and bed of crew. The purpose of this research is to know relation of ship sanitation with existence of vector and rodent on passenger ship. This type of research is quantitative with global observational analytical method and cross sectional design. The data collecting is done by observation on passenger ship that is 30 passenger vessel, data processing is done by Chi Square test between independent variable and dependent variable. The results showed that sanitation of kitchen, warehouse and bed room is related to the existence of vector and rodent. While the sanitation of the passenger room is all well categorized and can not be tested because it is homogeneous. Sanitation vessels by checking overall with good category 15 and bad 15 and chi square test results obtained p value = 0,009 that can be concluded that the existence of relation between sanitary vessel with existence of disease vector and rodent on passenger ship.